The Synthesis of Nanodispersed Magnetite Using Electrochemical Method - S.Z. Kalaeva; N.S. Yamanina; V.M. Makarov; I.N. Zaharova; A.M. Shipilin; A.N. Solovyova; M.E. Terzi (Журнал нано- та електронної фізики)
The purpose of the work was to obtain nanodispersed magnetite (Fe3O4) with fewer impurities comparing to its natural form. For this the electrochemical method of dissolution of steel sheets or shavings in the heated electrolyte was employed. In order to optimize the technological parameters of this process the structural and magnetic properties of the obtained materials were studied using powder X-ray diffraction and vibrational magnetometry techniques correspondingly.